2003
DOI: 10.1038/sj.hdy.6800315
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of sporophytic self-incompatibility in Senecio squalidus L. (Asteraceae) II: a spatial autocorrelation approach to determining mating behaviour in the presence of low S allele diversity

Abstract: We recently estimated that as few as six S alleles represent the extent of S locus diversity in a British population of the self-incompatible (SI) coloniser Senecio squalidus (Oxford Ragwort). Despite the predicted constraints to mating imposed by such a low number of S alleles, S. squalidus maintains a strong sporophytic self-incompatibility (SSI) system and there is no evidence for a breakdown of SSI or any obvious negative reproductive consequences for this highly successful coloniser. The present paper ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Glémin et al, 2005 compared genetic structure between the S-locus and SSR loci in five populations of Brassica insularis with a sporophytic SI system, and their results were consistent with these predictions. Although Brennan et al, 2003 found no significant spatial genetic structure at either the S-locus or allozyme loci in Senecio aqualidus, Leducq et al (2011) recorded reduced spatial genetic structure at the S-locus than at SSR loci in Arabidopsis halleri. In rosaceous species with a gametophytic SI system, Stoeckel et al (2008) and Holderegger et al (2008) found less genetic differentiation between populations at the S-locus than at SSR loci, although Schueler et al (2006) did not find any differences in the extent of spatial genetic structure between the two locus types.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Glémin et al, 2005 compared genetic structure between the S-locus and SSR loci in five populations of Brassica insularis with a sporophytic SI system, and their results were consistent with these predictions. Although Brennan et al, 2003 found no significant spatial genetic structure at either the S-locus or allozyme loci in Senecio aqualidus, Leducq et al (2011) recorded reduced spatial genetic structure at the S-locus than at SSR loci in Arabidopsis halleri. In rosaceous species with a gametophytic SI system, Stoeckel et al (2008) and Holderegger et al (2008) found less genetic differentiation between populations at the S-locus than at SSR loci, although Schueler et al (2006) did not find any differences in the extent of spatial genetic structure between the two locus types.…”
Section: Discussionmentioning
confidence: 91%
“…In Brassica insularis, Glémin et al (2005) compared the population structure at the S-locus with that indicated by selectively neutral loci, nuclear simple sequence repeats (SSRs or microsatellites); their data supported most of the theoretical predictions. In Senecio squalidus, spatial genetic structure within populations was found to be weak at both the S-locus and at allozyme loci for which variation seemed to be selectively neutral (Brennan et al, 2003), whereas genetic differentiation among populations was smaller at the S-locus than at the allozyme loci (Brennan et al, 2006). In Arabidopsis halleri, the spatial genetic structure within populations was weaker when determined on the basis of the S-locus than when SSR loci were considered (Leducq et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…Previous empirical studies, together with our own results, showed three contrasted types of situations: (1) no pattern of SGS whatsoever-neither at the S-locus nor at neutral marker loci (Brennan et al, 2003); (2) significant and consistent patterns of SGS at the S-locus and neutral markers (Schueler et al, 2006; population Nivelle in this study); (3) significantly higher extent of SGS at neutral marker loci as compared to the S-locus (populations Auby and Hautes-Fagnes in this study). Situation (1) could be due to the absence of SGS in the case of random dispersal, to recent demographic disturbance or to a lack of resolution of the analysis when sample sizes are small (for example, in the study of Brennan et al, 2003, in S. squalidus only 24 individuals were sampled).…”
Section: Interpretation Of Empirical Resultsmentioning
confidence: 98%
“…Two empirical studies investigated SGS within populations for both the S-locus and neutral loci. In a population of Senecio squalidus, Brennan et al (2003) found no significant decrease of genetic similarity between individuals with spatial distance, at neither the S-locus nor allozyme markers. In contrast, in a population of Prunus avium, Schueler et al (2006) found evidence for SGS at both the S-locus and microsatellite markers, with a similar extent of SGS for both types of loci.…”
Section: Introductionmentioning
confidence: 99%
“…There is also empirical evidence that the breakdown of SI may have far more complex causes than merely the number of S-alleles, as exemplified by plants that do not behave as they should according to this theory: In the highly successful colonizer Senecio squalidus, the SI system has been maintained despite a very low number of S-alleles (Brennan et al, 2003). Furthermore, other genetic and non-genetic (for example, environmental) factors have been shown to result in a 'leakiness' of SI systems (Reinartz and Les, 1994, and references therein), and even the developmental stage (age of flowers) can make SI a plastic trait (Mena-Alí et al, 2009).…”
mentioning
confidence: 99%